PENGARUH LINGKUNGAN KERJA, KEMAMPUAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI PJ. MURIA JAYA KUDUS - Nabila, Ismi; Suryoko, Sri; Listyorini, Sari (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2013)
Along with the rapid development of today's business world, the more visible the role of human resource management in an effort to grow the business. In the past twoÂ years,Â quantity of product below the standard in PJ. Muria Jaya Kudus keep increasing. So company must maintance the employee performance in order to reach company goals. This study aims to determine the influence of variable work environment, work ability and compensation on the performance of the production employees PJ Muria Jaya Kudus. This study population are permanent employees of the production, amounting to 38 people. This study uses census approach, where all members of the population be respondents. Measurement scale using a Likert scale. In the analysis of data using simple linear regression test and regression test with SPSS 20.00. The results showed that the work environment have a positive effect on employee performance, work ability have a positive effect on employee performance, and compensation have a positive effect on employee performance. work environment, work ability, and compensation are jointly contributing positively towards employee performance. Based on the results of this study concluded that the work environment, employability and compensation a positive influence on the performance of the production employees in PJ. Muria Jaya, either partially or simultants. From the results of this study suggested the company to improve the work environment related to air circulation and air temperature in the workspace; Improve employees ability to understand the rules and policies of the company. And expected to consider the wage increases granted to employees throughout the company are still in capability.